Intima-media thickness evaluation by B-mode ultrasound: Correlation with blood pressure levels and cardiac structures - Plavnik, Frida Liane [UNIFESP] (2000)
The aim of this study was to analyze the thickness of the intima-media complex (IMC) using a noninvasive method. The carotid and femoral common arteries were evaluated by noninvasive B-mode ultrasound in 63 normotensive and in 52 hypertensive subjects and the thickness of the IMC was tested for correlation with blood pressure, cardiac structures and several clinical and biological parameters. The IMC was thicker in hypertensive than in normotensive subjects (0.67 ± 0.13 and 0.62 ± 0.16 vs 0.54 ± 0.09 and 0.52 ± 0.11 mm, respectively, P<0.0001). In normotensive patients, the simple linear regression showed significant correlations between IMC and age, body mass index and 24-h systolic blood pressure for both the carotid and femoral arteries. In hypertensives the carotid IMC was correlated with age and 24-h systolic blood pressure while femoral IMC was correlated only with 24-h diastolic blood pressure. Forward stepwise regression showed that age, body mass index and 24-h systolic blood pressure influenced the carotid IMC relationship (r2 = 0.39) in normotensives. On the other hand, the femoral IMC relationship was influenced by 24-h systolic blood pressure and age (r2 = 0.40). In hypertensives, age and 24-h systolic blood pressure were the most important determinants of carotid IMC (r2 = 0.37), while femoral IMC was influenced only by 24-h diastolic blood pressure (r2 = 0.10). There was an association between carotid IMC and echocardiographic findings in normotensives, while in hypertensives only the left posterior wall and interventricular septum were associated with femoral IMC. We conclude that age and blood pressure influence the intima-media thickness, while echocardiographic changes are associated with the IMC.